Probing lncRNA–Protein Interactions: Data Repositories, Models, and Algorithms - Peng, Lihong; Liu, Fuxing; Yang, Jialiang; Liu, Xiaojun; Meng, Yajie; Deng, Xiaojun; Peng, Cheng; Tian, Geng; Zhou, Liqian (Frontiers in Genetics, 2020)
Identifying lncRNA-protein Interactions (LPIs) is vital to understanding various key biological processes. Wet experiments found a few LPIs, but experimental methods are costly and time-consuming. Therefore, computational methods are increasingly exploited to capture LPI candidates. We introduced relevant data repositories, focused on two types of LPI prediction models: network-based methods and machine learning-based methods. Machine learning-based methods contain matrix factorization-based techniques and ensemble learning-based techniques. To detect the performance of computational methods, we compared parts of LPI prediction models on Leave-One-Out cross validation (LOOCV) and five-fold cross validation. The results show that SFPEL-LPI obtained the best performance of AUC. Although computational models have efficiently unraveled some LPI candidates, there are many limitations involved. We discussed future directions to further boost LPI predictive performance.